Drugs and drug policy: the control of consciousness alteration - Mosher, Clayton James (SAGE, 2021)
"This engaging and throughly updated text provides a cross-national perspective on the use and regulation of both legal and illegal drugs. Drugs and Drug Policy examines and critiques drug policies in the United States and abroad in terms of their scope, goals, and effectiveness. Authors Clayton J. Mosher and Scott Akins also discuss the physiological, psychological, and behavioural effects of legal and illicit drugs; the patterns and correlates of use; theories of the causes of drug use; and the policies that govern that usage"--